ANALISIS PRIORITAS USAHATANI PERKEBUNAN DI KECAMATAN BESULUTU KABUPATEN KONAWE - Sofyan Al Razak; La Ode Alwi; La Ode Kasno Arif (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
Plantation farmers in Besulutu District were initially dominant in cultivating cocoa plantations, but as time went by, old cocoa plants combined with attacks by pests and diseases of the cocoa plants made the cocoa plants no longer productive so that in the end many farmers began to replace cocoa plants with oil palm plants. and also focus more on caring for their pepper plants. The population in this study included all plantation farmers (cocoa, oil palm, sago and pepper plantations) in three villages in Besulutu District, totaling 308 farmers and a sample from a population of 75 farmers determined using the Slovin method with an error rate of 10%. This research aims to determine the priority types of plantation crops to be cultivated in Besulutu District. This research uses Analytic Hierarchy Process or AHP analysis and Expert choisse11 software to obtain conclusions. The conclusion of this research shows that the priority plantation crop in Besulutu District, Konawe Regency is cocoa with the priority criteria being policy support criteria.